Validity of learning devices based on guided discovery learning model - Meisa Kurnia; Irwan Irwan; Yerizon Yerizon (International Conferences on Educational, Social Sciences and Technology)
One of mathematics learning purposes for students is having the capability or skill to solve a mathematics’ problem, as a means for students to sharpen accuracy, logical, critical, analitycal, and creative reasoning so that problem was not a problem anymore for students. For optimal learning process, it is necessary supported by relevant learning device. This is the basis for research in mathematics learning device development like lesson plan and students worksheet based on Guided Discovery Learning model where learners are also learning and thinking to solve their problems independently through the materials facilitated by teachers and teacher’s guidance. This was a development research which applied Plomp model. Based on the result of research, it could be concluded that guided discovery learning was valid.